Histone Demethylase KDM4C Stimulates the Proliferation of Prostate Cancer Cells via Activation of AKT and c-Myc - Lin, Ching-Yu (Cancers (Basel), 2019)
Our three-dimensional organotypic culture revealed that human histone demethylase (KDM) 4C, a histone lysine demethylase, hindered the acini morphogenesis of RWPE-1 prostate cells, suggesting its potential oncogenic role. Knockdown (KD) of KDM4C suppressed cell proliferation, soft agar colony formation, and androgen receptor (AR) transcriptional activity in PCa cells as well as reduced tumor growth of human PCa cells in zebrafish xenotransplantation assay. Micro-Western array (MWA) analysis indicated that KD of KDM4C protein decreased the phosphorylation of AKT, c-Myc, AR, mTOR, PDK1, phospho-PDK1 S241, KDM8, and proteins involved in cell cycle regulators, while it increased the expression of PTEN. Fluorescent microscopy revealed that KDM4C co-localized with AR and c-Myc in the nuclei of PCa cells. Overexpression of either AKT or c-Myc rescued the suppressive effect of KDM4C KD on PCa cell proliferation. Echoing the above findings, the mRNA and protein expression of KDM4C was higher in human prostate tumor tissues as compared to adjacent normal prostate tissues, and higher KDM4C protein expression in prostate tumors correlated to higher protein expression level of AKT and c-Myc. In conclusion, KDM4C promotes the proliferation of PCa cells via activation of c-Myc and AKT.